Relationship between body measurements and performance traits in boars - P B Conley III; T W Orwig; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Fourteen body measurements were taken on 259 boars at 65 lbs. and again at 250 lbs. determine the relationship of external body dimensions with certain performance traits. Correlations between body measurements and growth tended to be extremely low for most factors. Our results do not support using body measurements as v1sual indicators of growth. This study suggests that performance testing is still the best way to predict a particular animal's genetic potential.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Body measurements; Performance traits; Boars